(untitled) (Papeles, 2014)
This article provides a contextualization of teaching when we definy how this discipline caters to both the teaching and learning processes, and how this important recognition is important for the exercise of teaching. The relevance of reflection is in how discover the essence of teaching makes that the problem lies in the interpretation and putting this in context. Finally, we will show how the subject in educational contexts, needs teaching from the same interaction, relationship complemented by articulating what the teacher offers students and technological resources that today must foster a meaningful learning.